Analysis of Segmentation Profile on Online Shopping Consumers in Padang City Based on Demographic and Psychographic Characteristics - Utami, Wiry; Wati, Linda; Mulatsih, Listiana Sri; Nadhira, Lulu (Jurnal Manajemen, 2022)
Online shopping has become a more accessible way of purchasing. Customer segmentation play important role in online retailing industry. The main objective of this study is to analysis of segmentation profile of online shopping consumers in Padang City based on demographic and psychographic characteristics. This type of research was descriptive analysis. The data are subsequently related to demographics and psychographic. The sampling technique in this research was purposive sampling. Total samples in this research were 150. The data analysis technique used in this research was cluster analysis. We demonstrate that such cluster related to demographic as well as psychographic characteristics. The results of demographic segmentation, the majority of respondents are female (74.4%) and the most of respondents 21-30 years old. Cluster analysis was applied to segment the customer into eight clusters that have distinct online customer profiles. These segments are named as risk taking consumers, adventurous consumers, active consumers, practical consumers, socialite consumers, economical consumers, passive consumers and independent consumers.